(untitled) (Intent Research Scientific Journal, 2023)
JavaScript is a versatile and widely used programming language that powers the web. Its ecosystem is enriched by a vast array of libraries and frameworks, which extend its capabilities and streamline development processes. This abstract explores some of the most widely used libraries in the JavaScript ecosystem and discusses their key capabilities.